Analisis Faktor-Faktor Yang Mempengaruhi Minat Berinvestasi Di Pasar Modal Syariah Pada Asn Kota Langsa - Mastura; nurjanah; mhd. Yogi Ardin (Glossary : Jurnal Ekonomi Syariah, 2026)
This study analyzes the level of investment interest and the factors influencing civil servants in Kota Langsa toward the Islamic capital market following the 2025 MURI Record momentum. The study applies a qualitative approach with a case study design. Data were collected through semi structured interviews with 5 civil servants from different institutions. The findings indicate that investment interest is at an early stage and develops gradually. The MURI Record increased awareness and trust in the Islamic capital market. Interest is reflected in changes in perception, information seeking, and initial understanding of investment instruments. Investment activity remains limited and generally begins with small capital. The learning process occurs within limited time and is adjusted to work responsibilities. Factors influencing investment interest include personal motivation, religiosity, economic awareness, work environment, and access to digital information. The findings show that investment interest develops gradually through individual experience and evaluation.